Impact of Wireless Energy Transfer Strategies on the Secrecy Performance of Untrustworthy Relay Networks - Egashira, Edson Nobuyuki; Moya Osorio, Diana Pamela; Benitez Olivo, Edgar Eduardo (Institute of Electrical and Electronics Engineers (IEEE), 2022)
This work investigates the secrecy outage performance of a dual-hop relaying network with an untrustworthy energy-constrained amplify-and-forward relay. A destination-based jamming technique is adopted in order to prevent the relay from decoding confidential messages from the source. Additionally, three time switching-based wireless energy transfer strategies are investigated for supplying power to the relay. For these three strategies, we derive simple closed-form asymptotic expressions for the secrecy outage probability at high signal-to-noise ratio. Moreover, we provide analytical expressions for the optimum power allocation factor for the information transmission phase. Finally, Monte Carlo simulations are carried out to verify the theoretical results through different illustrative cases.
Keywords: Communication system security; Destination-based jamming; Jamming; physical layer security; Relay networks (telecommunication); Resource management; secrecy outage probability; Signal to noise ratio; SWIPT; untrustworthy relay; Wireless communication; Wireless sensor networks